TEPAT Innovation Program in Managing Hypertension among Elderly at Piladang Public Health Center - Sri Siswati; Muthia Khairunnisa; Luvita Aura Putri; Robi Tri Nanda; Ayu Salsabila; Widelina Yulianty Devita; Putri Aulia Azzahra; Caesar Rani Batavia; Khairunnisa Khairunnisa (Warta Pengabdian Andalas, 2024)
Hypertension is a degenerative disease that is called a silent killer, meaning that this disease does not show symptoms before a health examination. Based on the 2018 West Sumatra Province Riskesdas Report, Solok Regency was ranked second in West Sumatra Province with a total of 14,414 cases. Piladang Public Health Center in 2022 shows that hypertension is the fourth most common disease, namely 522 cases with coverage of hypertension services according to standards of only 10% of the target of 100%. This activity aims to increase knowledge and awareness elderly about hypertension through education and demonstrate massage therapy procedures. This activity was carried out in Jorong Tambun Ijuk Hall on September 30, 2023, attended by 31 elderly. Education is delivered using a lecture method about hypertension, a demonstration method for the TEPAT (Terapi Pijat Hipertensi Minggat) program, and a discussion method. It is hoped that the results of this activity can be used to increase understanding of hypertension and hypertension massage therapy in the elderly in the Piladang Public Health Center working area